2021
DOI: 10.3390/s21144770
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Assessment of Balance and Falls Risk Using a Smartphone and Machine Learning

Abstract: Assessment of health and physical function using smartphones (mHealth) has enormous potential due to the ubiquity of smartphones and their potential to provide low cost, scalable access to care as well as frequent, objective measurements, outside of clinical environments. Validation of the algorithms and outcome measures used by mHealth apps is of paramount importance, as poorly validated apps have been found to be harmful to patients. Falls are a complex, common and costly problem in the older adult populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Patients indicated that the remote monitoring system was easy to use and improved quality of life. Greene et al [ 49 ] used a smartphone app and machine learning to assess fall risk in patients, finding that fall assessments provided by the app were correlated with patients’ self-reported fall history. Oagaz [ 50 ] developed and tested a virtual reality system that was able to perform eye tracking and motion analysis, suggesting it may be useful in diagnosing patients with neurocognitive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Patients indicated that the remote monitoring system was easy to use and improved quality of life. Greene et al [ 49 ] used a smartphone app and machine learning to assess fall risk in patients, finding that fall assessments provided by the app were correlated with patients’ self-reported fall history. Oagaz [ 50 ] developed and tested a virtual reality system that was able to perform eye tracking and motion analysis, suggesting it may be useful in diagnosing patients with neurocognitive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other fall risk apps, Steady, Steady-MS, and Steady-Wheels are some of the few apps that have been designed for specific clinical populations and evaluated for their validity, reliability, and usability. Greene et al ( 26 ) used machine learning methods to develop an algorithm for predicting falls using mobile technology but did not test their app with older adult users. Mansson et al ( 27 , 28 ) developed an app to measure leg strength and balance and tested its usability with older adults but did not measure other fall risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones can capture voice and tremor and, and through machine learning, we can monitor or even diagnose Parkinson' s disease [41][42][43] . Assessing balance and risk of falls using a validated smartphone app can increase safety and reduce the number of falls in older adults 44 .…”
Section: Discussionmentioning
confidence: 99%